ANALYSIS OF FACTORS AFFECTING THE FINANCIAL RESULT FROM THE SALE OF PRODUCTS - Djumabaeva, Nurzada; Abishov , Mukhammed (Educational Research in Universal Sciences, 2023)
This scientific article aims to analyze the various factors that influence the financial outcome of product sales. The financial success of any business depends on several key variables, including market demand, pricing strategy, marketing efforts, competition, and customer satisfaction. By comprehensively examining these factors, organizations can make informed decisions and develop effective strategies to maximize their financial results from product sales. This article investigates the impact of each factor and provides insights into how businesses can enhance their financial outcomes.